Pemberdayaan Keluarga dalam Meningkatkan Ketahanan Keluarga melalui Program Pendampingan Caregiver Pasien Stroke di Rumah - Fadilah, Nikmatul; Minarti , Minarti; Wiyatno, Eko Rustamaji (Health Community Engagement, 2021)
Health problems of family members due to stroke can be a stressor for family life. Tensions and care burdens are triggered by several conditions, including unpreparedness to care for due to limited knowledge, skills, time, and funding. Prolonged stress will not only affect the caregiver, but also have an impact on the recovery of stroke patients. The objectives of community service are to improve the care ability of the caregivers for stroke patients at home, achieve caregiver adaptive coping behavior, monitor the caregiver's health status, and increase the patient's activity daily living (ADL) ability. Community service was carried out by mentoring 57 caregivers of stroke patient in the work area of the Perak Timur Community Health Center in Surabaya. The methods are through health education, skills training, health checks, mentoring for 2 weeks, and evaluation. Media activities used stroke care modules for caregivers, questionnaires, Katz Index, and health check tools. The results of the assessment of the ability to care for stroke patients, caregiver coping behavior, and ADL ability of stroke patients showed an increase even though it was still minimal. Caregiver health data shows health risks experienced including blood pressure in most hypertension categories, as well as having a history of hypertension, diabetes, and hypercholesterolemia. Knowledge of caring for stroke patients that has been gained during hospitalization needs follow-up and evaluation. Assistance is a solution to minimize stressors for families with stroke patients so that they can achieve family resilience and optimal quality of life.